Students' engineering experience and aspirations within STEM education in Hong Kong secondary schools. (2020) - Kutnick, Peter; Lee, Betty Pok-Yee; Chan, Rosanna Yuen-Yan; Chan, Cecilia Ka Yuk
Highlights: Asian focus concerning students' engineering aspirations within STEM education. School-based engineering makes only a small contribution to STEM education. Younger students were excluded from school-based engineering activities. Students' engineering aspirations largely supported via personal pathways. Traditional e/STM subjects still characterize STEM reforms and hinder aspirations. Abstract: This study questions whether Hong Kong (HK) students' engineering aspirations are facilitated within their secondary school STEM curriculum or elsewhere. HK students perform strongly on international science and mathematics assessments, although its economy is reliant on a dwindling number of engineers. We consider STEM education metaphors, recent government attempts to improve STEM education and lack of Asian STEM literature. A representative twenty-four students (sex, age, secondary school type) were interviewed to elicit school/home e/STM (engineering within/STM subjects) experiences and aspirations. Thematic content analyses found: e/STM aspirations most susceptible to (pathway-based) home and cultural inequalities; younger students excluded from engineering interests; and, inhibiting in-school activities/pedagogies. Within this high-performing Asian society, inhibitors to engineering engagement were similar to current Western findings.